A cost-effective protocol for monitoring birds using autonomous recording units: a case study with a night-time singing passerine. Issue 3 (3rd July 2018) - Pérez-Granados, Cristian; Bota, Gerard; Giralt, David; Traba, Juan
ABSTRACT: Capsule: We describe an effective monitoring protocol for detecting wildlife presence using autonomous recording units (ARUs) under different density scenarios. Aims: To describe an effective protocol for monitoring a night-time singing passerine, the Dupont's Lark Chersophilus duponti, using ARUs. Methods: We estimate, using both simulations and field-collected data, the number of devices needed to reliably detect the species under different density scenarios and to assess recording time and the number of working days needed to ensure species detection. We placed between four and six ARUs in three Dupont's Lark populations with different bird densities. Devices were programmed to record for 90 minutes per day for four consecutive days. ARUs were deployed between April and June of 2017. Results: We found large differences in the number of recorders needed to detect species presence under different density scenarios, with more ARUs required in less dense populations. The number of ARUs needed to be differed between estimates obtained by simulations and with field data. This could be related to movements of the monitored species while they were singing. According to our results, the monitoring period for detecting the Dupont's Lark could be as little as one hour of recording (from one hour before dawn to dawn) and two monitoring days, the minimum monitoring time needed to detect the species in all populations surveyed, regardless of density scenarios. Conclusion: Our results cannot be directly extrapolated to other singing species since singing behaviour and characteristics greatly differ between species. We describe five logical steps to develop effective wildlife monitoring protocols using ARUs for detecting species presence, which may be helpful for future studies and with different species.